INOVASI PELAYANAN PUBLIK MELALUI SOLO DESTINATION DI KOTA SURAKARTA, JAWA TENGAH - Sari, Yunita Ratna (Sawala : Jurnal Administrasi Negara, 2019)
Solo destination is a public service innovation from the  Surakarta City Communication dan Information Departement in the form of a mobile based application. The application in Solo Destination consists of various features including culinary, hotels, public facilities, shopping centers, cultural events, community services, children?s radio and historic sites. The launching of  Solo Destination application service received the MURI award as the first city in Indonesia to provide technology based tourism services through the application. The purpose of this researh is to explain the innovation of public service in the field tourism through Solo Destination. The method used is desk research that utilizes secondary data as a source of literature. The results of the study show taht the implementation of Solo Destination in the Surakarta City provides positive benefits for all parties including the Surakarta City Goverment to provide public services to the public quickly. For the public and tourists can provide services on the potential of Surakarta City easliy and completely